Numinous Fields: Perceiving the Sacred in Nature, Landscape, and Art - Akkach, Samer; Powell, John (Middle East and Islamic Studies E-Books Online, Collection 2024., 2024)
Numinous Fields has its roots in a phenomenological understanding of perception. It seeks to understand what, beyond the mere sensory data they provide, landscape, nature, and art, both separately and jointly, may mean when we experience them. It focuses on actual or potential experiences of the numinous, or sacred, that such encounters may give rise to. This volume is multi-disciplinary in scope. It examines perceptions of place, space, nature, and art as well as perceptions of place, space, and nature in art. It includes chapters written by art curators, and historians and scholars in the fields of landscape, architecture, cultural geography, religious studies, philosophy, and art. Its chapters examine ideas, objects, and practices from the ancient time of Aboriginal Australians' Dreaming through to the present. The volume is also multi-cultural in scope and includes chapters focussed on manifestations of the sacred in indigenous culture, in cultures influenced by each of the world's major religions, and in the secular, contemporary world. Foreword by Jeff Malpas Contributors: Samer Akkach, James Bennett, Veronica della Dora, Alasdair Forbes, Virginia Hooker, Philip Jones, Russell Kelty, Muchammadun,Tracey Lock, Ellen Philpott-Teo, John Powell, Rebekah Pryor, Wendy Shaw.